Utilitarianism in The Complete Systematic Land Registration (PTSL) Program Policy - Abdillah, Sulaiman; Kurniasih, Denok; Midhol, Ahmad Baihaqi (JPW (Jurnal Politik Walisongo), 2025)
This research discusses the application of the principle of utilitarianism in the Complete Systematic Land Registration (PTSL) Program policy in Indonesia which aims to provide legal certainty and improve community welfare through land certification. Data shows that until 2021, there are 54 million parcels of land that have not been certified, which has the potential to cause agrarian conflicts and gaps in economic access. The utilitarianism approach is used to analyze the impact of the program on the benefits for the wider community. This research uses a qualitative method with a literature review approach and uses secondary data from various official sources. The results show that PTSL has provided significant benefits, such as reduced land conflicts and improved economic access. On the other hand, there are still challenges in implementation, such as illegal levies and lack of transparency. Therefore, it is necessary to emphasize the importance of monitoring and improving the quality of program implementation to maximize benefits for the community.